A scalable wideband speech codec using the wavelet packet transform based on the internet low bitrate codec. (March 2019) - Seto, Koji; Ogunfunmi, Tokunbo
Highlights: A packet-loss robust scalable wideband speech codec is proposed. Performance is improved using the wavelet transform instead of the MDCT. The proposed codec outperforms the state-of-the-art codec in objective tests. High performance of the proposed codec is confirmed in subjective tests. Abstract: Most recent speech codecs employ code excited linear prediction (CELP) and transmit side information to improve speech quality under packet loss. Another approach to achieve high robustness to packet loss is to use the frame independent coding scheme based on the internet low bitrate codec (iLBC). The scalable wideband speech codec based on the iLBC was previously presented and outperformed G.729.1 at most bit rates according to the objective quality. This paper presents improvements to the previous work. Specifically, we employ the wavelet packet transform (WPT) instead of the modified discrete cosine transform (MDCT) to enhance the quality, and evaluate the proposed codec based on both the objective and subjective quality measures. The objective quality evaluation results show that clear improvement is achieved and that the proposed codec outperforms G.729.1 at the bit rate of 18 kbps or higher under clean channel conditions and has higher robustness to packet loss than G.729.1. The informal subjective test results also show similar trends.